Tertiary treatment for psychiatric comorbidity in headache patients - Savarese, M. (Springer-Verlag, 2005)
The presence of significant and confounding psychiatric comorbidity is greater in patients attending headache clinics than in headache patients from the general population. The frequent comorbidity of headache with generalized anxiety disorder can take advantage of the administration of benzodiazepines. With regard to depression–related headache, it’s wellknown that the antidepressive drugs can improve migraine as well as tension–type headache. Antiepileptic drugs give one more good opportunity. The recognition of a psychiatric comorbidity is mandatory for an accurate management of the patient beacause prevents the clinicians from using any drug that might be dangerous for a mysdiagnosed psychiatric disturbance and often permits to administer medications that can efficaciously control both headache and psychiatric disorders.